Sub-Tenon's bupivacaine injection is superior to placebo for pediatric strabismus surgery: A meta-analysis - Weijuan, Zeng; Zonghuan, Li; Qian, Wang; Xizhi, Deng; Bin, Jiang; Min, Ke (Frontiers in Pediatrics, 2023)
Background: The effect of sub-Tenon’s bupivacaine injection for pediatric strabismus surgery is controversial. The objective of this meta-analysis is to compare the application of sub-Tenon’s bupivacaine and placebo injection for strabismus surgery. Methods: We searched the databases (Pubmed, Cochrane library and EMBASE) and reference lists systematically. Randomized controlled trials (RCTs) comparing sub-Tenon’s bupivacaine and placebo injection for strabismus surgery were included. The methodological quality was evaluated by the Cochrane risk of bias (ROB) tool. Outcome measurements were pain score, oculocardiac reflex (OCR), additional drug consumption and related complications. RevMan 5.4 was used for the statistical analysis and graph preparation. For the outcomes that are not suitable for statistical analysis, descriptive analysis was performed. Results: A total of 5 RCTs with 217 patients were finally identified and analyzed. Sub-Tenon’s bupivacaine injection showed pain relief within 30 minutes after operation. But with the extension of time, the analgesic effect gradually disappeared at 1 hour. It can reduce the incidence of OCR, vomiting and supplementary drug requirements. However, in terms of nausea, there is no difference between the two groups. Conclusion: Sub-Tenon’s bupivacaine injection can relieve short-term postoperative pain, reduce the incidence of OCR and vomiting, and reduce the use of drugs in strabismus surgery.